الملخص: إن اتجاه الإدارة إلى استخدام أساليب إستراتيجية حديثة مثل إدارة سلسلة الإمداد، خلق مشكلة جديدة لإدارة الأداء نتيجة قصور نظم قياس الأداء التي تعتمد على المقاييس التقليدية (المالية فقط) بالدور المطلوب منها، وأصبح تطوير مقاييس أداء ملائمة للقيام بذلك - عمر, د.أقاسم; نسيمة, أ.لعرج مجاهد (Recherches économiques et managériales, 2015)
الملخص: إن اتجاه الإدارة إلى استخدام أساليب إستراتيجية حديثة مثل إدارة سلسلة الإمداد، خلق مشكلة جديدة لإدارة الأداء نتيجة قصور نظم قياس الأداء التي تعتمد على المقاييس التقليدية (المالية فقط) بالدور المطلوب منها، وأصبح تطوير مقاييس أداء ملائمة للقيام بذلك من أهم التحديات التي تواجه منظمات اليوم، وعليه يهدف هذا المقال إلى التعرف بداية على مفهوم تقييم وقياس أداء سلسلة الإمداد، مقومات نجاحه ومختلف المؤشرات والنماذج المساعدة المستخدمة في قياسه، وقد خلص المقال إلى أن وجود سلسلة إمداد فعالة يؤدي إلى تحسين ربحية المؤسسة ولا يتحقق ذلك إلا بتوفر مقاييس أداء فعالة. الكلمات الدالة : سلسلة الإمداد، قياس الأداء، مؤشرات. Abstract:    The direction of the administration's strategy to use modern methods such as supply chain management, creating a new problem for the management of performance as a result of lack of performance measurement systems which rely on traditional measures (financial only) the role required from it, and the development of performance metrics become convenient to do so of the most important challenges facing organizations today. Based on this, the article  aims to identify the concept of assessing and measuring the performance of the supply chain, the elements of its success and identify the various indicators and models used to measure the performance of the supply chain. The research paper has concluded that, the existence of an effective quality management leads to improve the profitability of the organization and this cannot be achieved except through the availability of effective performance metrics . Keywords: Supply chain, measurement  performance, indicators